Adaptation | A Reflection on Contemporary Chinese Architecture (In four case-studies) - Bert Hugo Raf De Muynck (IPTEK Journal of Proceedings Series, 2017)
Reflecting upon a decade of engaging with, researching, writing, curating and discussing critical and contemporary Chinese architectural developments (profession and projects), the author presents ‘adaptation’ as a modus operandus for Chinese architects to bypass both rapid cultural changes as well as a volatile and demanding building construction climate.  Seeking to understand the underlying concepts, methods and motives behind selected projects of four distinct contemporary practices (Amateur Architecture Studio, Atelier Chen Haoru, ZAO/standardarchitecture, Zhao Yang studio) the author discusses how these adapt to progress. Besides, the aforementioned practices encompass in China three distinct generations of architects, all practicing, to a large extent, in a similar spatial, social and economical environment. Focusing on the passage of time and the progress of the profession, rather than pointing out a figure or structure frozen in time, and through case-studies linked to the authors’ exhibition ‘ADAPTATION – architecture and change in China’ (Venice Architecture Biennale 2014), the paper seeks to discuss how architects effectively adapt and transform their thinking, practice and design in relation to ongoing demands and insights. Relating these to professional discourse, use of local materials and knowledge, to the volatility of clients, governments and markets, these alternative practices (alternative to the dominance of design institutes, to generic solutions and to Western, modernist, theories and practice) aspire to keep control over the design process. Across the four discussed practices, similarities in approach, materiality, methodology, educational and environmental concerns are contrasted with differences in architect-client relation, public appreciation, public and personal influence, laws, academic discourse. Through the lens of understanding how architects transform their modus operandi, tentatively the concept of ‘in(ter)depedent practices and projects’ (or mutual reliance between different generations of independent architects) can be explored.